2016
DOI: 10.1002/app.44006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supercritical carbon dioxide treatment on the morphology of poly(l‐lactide)

Abstract: Synthetic l‐lactide random copolymers can be employed as controlled release materials when prepared using supercritical carbon dioxide (scCO2), since they are biodegradable via hydrolysis. To determine the effects of thermal properties on polymer performance following scCO2 processing, three types of poly(l‐lactide) having different properties were assessed. The Tm of one poly(l‐lactide) sample (H‐100) was found to be approximately 170 °C over the processing pressure range from 8 to 18 MPa, while a second samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…The XRD spectrum can provide information regarding percent crystallinity as well as interplanar spacing, and so XRD data were used to assess variations between copolymers. It has been reported that poly(L‐LA) generates three main XRD peaks (2 θ : 16.7°, 19.1°, and 22.4°) and that these become more intense as the scCO 2 processing temperature is increased, indicating increasing crystallinity . Similar results were obtained for the poly(L‐LA‐ ran ‐VL) specimens, and the results for the 91/9 and 73/27 specimens are shown in Figure A,B.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The XRD spectrum can provide information regarding percent crystallinity as well as interplanar spacing, and so XRD data were used to assess variations between copolymers. It has been reported that poly(L‐LA) generates three main XRD peaks (2 θ : 16.7°, 19.1°, and 22.4°) and that these become more intense as the scCO 2 processing temperature is increased, indicating increasing crystallinity . Similar results were obtained for the poly(L‐LA‐ ran ‐VL) specimens, and the results for the 91/9 and 73/27 specimens are shown in Figure A,B.…”
Section: Resultssupporting
confidence: 81%
“…In this work, an equivalent effect was obtained by scCO 2 processing at 14 MPa and 120°C in the case of the copolymer containing 9 mol% VL. In a previous investigation, poly(L‐LA) was treated with scCO 2 only at 80°C and 14 MPa, but the same effect was observed.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…On the contrary, at low temperature, with shear and longer characteristic times of thermal agitation, molecules have more time to reorganise, facilitating the crystallization . It is known that CO 2 has an effect on the crystallinity and crystallization rate of PLA . Nofar et al .…”
Section: Resultsmentioning
confidence: 99%
“…They also observed that crystallinity was affected by the density of nuclei on the molecular mobility of PLA and by the resultant plasticization effect of CO 2 at different CO 2 pressure. For Tsutsumi et al ., DSC results have shown that the PLA crystallinity changes depend on temperature and pressure during CO 2 treatment. This is due to the rearrangements of the lamellar structures in the crystalline region.…”
Section: Resultsmentioning
confidence: 99%